Про техніку виготовлення сарматських мечів та кинджалів із Середнього Подніпров’я - Вознесенська, Г.О.; Козловська, Н.Ф.; Корецька, С.А. (Археологія, 2002)
У статті наведено результати технологічного вивчення п'яти клинків сарматських мечів та кинджалів із колекції КДІМ. Авторы исследовали 5 клинков мечей и кинжалов с кольцевыми навершиями на рукояти и прямым перекрестием из коллекции КГИМ. Все они найдены на территории Среднего Поднепровья и датируются I в. до н. э. На основе металлографических исследований проведена реконструкция технологических схем изготовления клинков. В итоге можно заключить, что клинки мечей были изготовлены приемами свободной кузнечной ковки из полос кричного железа, которые имели следы незначительной первичной науглероженности, или из полос сырцовой стали с неравномерным содержанием и распределением углерода. Анализ клинка из с. Березинцы позволяет утверждать, что сарматские кузнецы, по крайней мере в среднесарматское время, использовали операцию вторичной цементации заготовки с целью улучшения качеств клинка.
Критически относясь к выводам Б.А. Шрамко и его коллег, которые исследовали 4 сарматских клинка, авторы статьи считают, что только дальнейшие исследования позволят ответить на вопрос о путях формирования производственных традиций кузнечного производства сарматов. The authors have analyzed five blades of the swords and daggers with the circled tops of the handles and with the straight cross from the collection of the Kyiv National Historical Museum. All of them are found on the territory of the Middle Dnieper and are dated to the 1st century BC - the 1st century AD. On the grounds of the metallographic investigations, the reconstruction of the technological schemes of blade manufacturing was made. Consequently, a conclusion may be made that the blades of swords were manufactured by the methods of free smithery either from the lines of bloom iron, which had been slightly primarily carbonated or from the lines of raw steel with the uneven contents and distribution of carbonate. The analysis of the blade from the village of Berezintsy allows us to confirm that the Sarmatian blacksmiths at least in the Middle Sarmatian phase used the operation of secondary cementation of the half-manufactured product, aiming to improve the working qualities of the blade.
Being critical of the conclusions of B.A. Shramko and his colleagues, who had analyzed four Sarmatian blades, the authors of the article consider that only further investigations will manage to solve the problem of the ways of forming the manufacturing traditions of the Sarmatian smithery.